Efeito da gordura do leite de cabra sobre parâmetros bioquímicos, marcadores de estresse oxidativo e comportamento de ratos exercitados - Barbosa, Mayara Queiroga (2018)
Goat's milk is a food with a potential functional effect because of its rich nutrient composition. Among them, medium chain fatty acids (MCFAs) and conjugated linoleic acid (CLA), which have shown effects on the increase of lean mass and modulation in the biochemical pattern and oxidative stress. The objective of this study was to evaluate the effects of diets with goat's milk fat associated with physical training on physical changes, biochemical parameters, oxidative stress markers and behavioral parameters of exercised rats. Male rats (70 days of life) were randomly assigned to six groups (n = 10): sedentary (CON) and exercise (CON-EX); sedentary (GM) and exercised goat's milk fat (GM-EX); goat's milk fat with increased levels of sedentary CLA (GM-CLA) and exercised (GM-CLA-EX). Body weight, blood glucose, plasma lipid profile, body composition, markers of oxidative stress (MDA and glutathione - GSH) in the muscle and brain, and behavioral anxiety parameters in the Open Field and Maze Elevated tests were evaluated. Regarding the behavioral parameters, GM-CLA-EX presented higher rearing compared to GM-CLA. Grooming was higher in GM-EX compared to the other groups (p <0.05). The frequency of the entries and the time of stay in the open arms were higher in the sedentary groups CON, GM, GM-CLA, in relation to the groups exercised (p <0.05). However, the time spent in the open arms and central area were significantly higher in GM, compared to CON and GM-CLA (p <0.05). MDA levels in the brain were lower in GM compared to CON (p <0.05), but an increase in CON-EX was observed in relation to CON, GM-EX and GMCLA-EX groups. The sedentary and exercised groups that consumed goat's milk fats showed high levels of GSH in the brain, in relation to the control groups (p <0.05). Body weight was lower in the groups fed goat's milk fat, but the GM-EX presented lower weight gain (p <0.05), indicating that the CLA content did not influence the lower weight gain. The mesenteric, retroperitoneal and carcass fat percentages decreased in GM-EX and GM-CLA-EX (p <0.05). The glycemia was higher in the GM and GM-CLA groups, but in the GM-EX and GM-CLAEX groups, the levels were lower (p <0.05). HDL cholesterol in GM-EX was higher than GM (p <0.05). In the muscle, MDA levels were higher in sedentary GM and GM-CLA, compared to NOC (p <0.05), and GM-EX presented higher results in all groups analyzed (p <0.05). GSH levels were higher in the GM and EX-groups, compared to the other groups (p <0.05). These results indicate that the effects of diet with goat milk fat associated with physical training promoted beneficial effects, such as reduction of body weight gain, repercussions on reduction of body fat, reduction of risk factors for atherosclerosis, and induced increased glutathione in the muscle. However, the reduction of MDA levels and the increase of GSH in the brain were associated with decreased anxiety behavior only in the sedentary groups fed with goat's milk fat. The physical training promoted an increase in anxiety behavior and the CLA content in the diets did not interfere in these results.